2023
DOI: 10.1093/tas/txad122
|View full text |Cite
|
Sign up to set email alerts
|

The effects of concurrent increases in supplementation of calcium and phytase on growth performance, balance of Ca and P, and bone mineralization in nursery pigs

Hengxiao Zhai,
Jon Bergstrom,
Jingcheng Zhang
et al.

Abstract: The objective of this study was to investigate the effects of concomitantly increasing supplementation of Ca and phytase on growth performance, balance of Ca and P, and bone mineralization in nursery pigs. There were 8 experimental diets. The positive control (PC) 1 and 2 were formulated to contain 0.64 and 0.85% total Ca, respectively, whereas the dietary concentrations of other nutrients were identical and adequate. The negative control (NC) was deficient in total Ca (0.48%) and total P (0.41%). Five combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In fact, P is an indispensable nutrient needed for normal growth, and it plays important roles in vital functions, such as energy and amino acid metabolism, protein synthesis, and maintaining acid–base balance [ 27 , 28 , 29 , 30 ]. Several studies have reported improvements in performance when phytase was used in piglets and growing pigs [ 21 , 31 , 32 , 33 , 34 , 35 ]. In the current study, the addition of phytase at 500 FTU/kg diet improved the growth performance and feed efficiency of nursery and growing–finishing pigs fed diets reduced in digestible P and Ca.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, P is an indispensable nutrient needed for normal growth, and it plays important roles in vital functions, such as energy and amino acid metabolism, protein synthesis, and maintaining acid–base balance [ 27 , 28 , 29 , 30 ]. Several studies have reported improvements in performance when phytase was used in piglets and growing pigs [ 21 , 31 , 32 , 33 , 34 , 35 ]. In the current study, the addition of phytase at 500 FTU/kg diet improved the growth performance and feed efficiency of nursery and growing–finishing pigs fed diets reduced in digestible P and Ca.…”
Section: Discussionmentioning
confidence: 99%